Bt, Not a Threat to Propylea japonica - Zhao, Chenchen; Wu, Linke; Luo, Junyu; Niu, Lin; Wang, Chuanpeng; Zhu, Xiangzhen; Wang, Li; Zhao, Peng; Zhang, Shuai; Cui, Jinjie (Frontiers in Physiology, 2020)
Given the ever-increasing commercial planting of transgenic plants across the world, an evaluation of their impacts on nontarget organisms is as an important part of the risk assessment process. Propylaea japonica is a dominant important nontarget prevalent predator and a pollen feeder insect in Bt cotton fields; thus, it is directly to Bt protein directly. However, the effect of Bt proteins on P. japonica has received scant attention. In this study, the effects of Cry1Ac and/or Cry2Ab proteins on P. japonica were investigated from three aspects. First, no significant differences in the diversity of the microbiota nor change in species composition and community structure were observed among Cry protein treatments. Firmicutes was the most abundant bacterial phylum present in P. japonica, followed by Proteobacteria and Actinobacteria. The most abundant genus was Staphylococcus. Second, the expression levels of the detoxification and digestion-related genes did not change significantly in any Cry protein treatment. Third, none of the Cry proteins affected the population fitness of P. japonica. These results indicated that P. japonica was not sensitive to Bt proteins, suggesting that growing Bt cotton expressing Cry1Ac and/or Cry2Ab will pose negligible risks to P. japonica.